Exosome in HBV infection: current concepts and future perspectives - Yuan, XueLan; Huang, ChunXia; Ran, Yan (Frontiers in Cellular and Infection Microbiology, 2025)
Exosomes are nanoparticles delimited by a lipid bilayer that are secreted by a wide variety of cells. They play a significant role in the pathophysiological processes associated with HBV infection, which poses huge burdens for public health. Emerging evidence has been demonstrated that exosomes are extensively associated with the replication and transmission processes of HBV. In this review, we outline the process of exosome production, composition and function. Moreover, we elaborate on the essential role of exosomes in the pathology processes of HBV infection. Exosomes could serve as essential biomarkers for early detection of HBV infection and HBV-related diseases. Finally, we outline the therapeutic potential of exosomes in anti-HBV therapy, which may provide novel insights into the prevention and treatment of HBV.